Effect of Long-Term Metformin and Lifestyle in the Diabetes Prevention Program and Its Outcome Study on Coronary Artery Calcium. Issue 1 (4th July 2017) - Goldberg, Ronald B.; Aroda, Vanita R.; Bluemke, David A.; Barrett-Connor, Elizabeth; Budoff, Matthew; Crandall, Jill P.; Dabelea, Dana; Horton, Edward S.; Mather, Kieren J.; Orchard, Trevor J.; Schade, David; Watson, Karol; et al.
Abstract : Background: Despite the reduced incidence of coronary heart disease with intensive risk factor management, people with diabetes mellitus and prediabetes remain at increased coronary heart disease risk. Diabetes prevention interventions may be needed to reduce coronary heart disease risk. This approach was examined in the DPP (Diabetes Prevention Program) and the DPPOS (Diabetes Prevention Program Outcome Study), a long-term intervention study in 3234 subjects with prediabetes (mean±SD age, 64±10 years) that showed reduced diabetes risk with lifestyle and metformin compared with placebo over 3.2 years. Methods: The DPPOS offered periodic group lifestyle sessions to all participants and continued metformin in the originally randomized metformin group. Subclinical atherosclerosis was assessed in 2029 participants with coronary artery calcium (CAC) measurements after an average of 14 years of follow-up. The CAC scores were analyzed continuously as CAC severity and categorically as CAC presence (CAC score >0) and reported separately in men and women. Results: There were no CAC differences between lifestyle and placebo intervention groups in either sex. CAC severity and presence were significantly lower among men in the metformin versus the placebo group (age-adjusted mean CAC severity, 39.5 versus 66.9 Agatston units, P =0.04; CAC presence, 75% versus 84%, P =0.02), but no metformin effect was seen in women. In multivariate analysis, the metformin effect in men was not influenced by demographic, anthropometric, or metabolic factors; by the development of diabetes mellitus; or by use/nonuse of statin therapy. Conclusions: Metformin may protect against coronary atherosclerosis in prediabetes and early diabetes mellitus among men. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00038727. Abstract : Supplemental Digital Content is available in the text.